PENGARUH LAJU ALIR UDARA, FAKTOR UDARA DAN SUHU TERHADAP KOMPOSISI GAS - Djeni Hendra (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
The result of gasification study using Albazia falcataria and Eucalyptus deglupte wood is reported in this paper, using fluidized bed system with an air flow rate varied between 2,8 - 4.0 m3/hr. air factor between 0.22 - 0.34 and bed temperature ranging from 742 - 895ᵒC.The aim of the study is to obtain the best treatment is the proses of fluidized bed. The result shows that the gascous product (%. Volume ) for Albazia falcateria Varies from 51.81 - 61.94 % (N2), 0.16-0,75 % (O2), 13.52- 19.13 % (CO2), 10.05 - 13.00 % (CO) , 4.19 - 6.41 % (H2) , 2. 2 7 - 5. 87 % (CH4). The figures for Eucalyptus deglupta were 54. 55 - 58; 06 % (N2) , 0.14 - 0. 18 % O2), 16.09- 18.81 % (COz), 11. 22 - 13.06 % (CO) , 7. 72 - 9. 73 (H2), 3.83 - 4.93 % (CH4).in addition C2H4 and C2H6 gas were produced in small quantity from each species.